Membrane-bound IL-12 and IL-23 serve as potent mucosal adjuvants when co-presented on whole inactivated influenza vaccines - Khan, Tila (BioMed Central, 2014)
BACKGROUND: Potent and safe adjuvants are needed to improve the efficacy of parenteral and mucosal vaccines. Cytokines, chemokines and growth factors have all proven to be effective immunomodulatory adjuvants when administered with a variety of antigens. We have previously evaluated the efficacy of membrane-anchored interleukins (IL) such as IL-2 and IL-4 co-presented as Cytokine-bearing Influenza Vaccines (CYT-IVACs) using a mouse model of influenza challenge. FINDINGS: Here, we describe studies evaluating the parenteral and mucosal adjuvanticity of membrane-bound IL-12 and IL-23 CYT-IVACs in young adult mice. Mucosal immunization using IL-12 and IL-23 bearing whole influenza virus vaccine (WIV) was more effective at eliciting virus-specific nasal IgA and reducing viral lung burden following challenge compared to control WIV vaccinated animals. Both IL-12 and IL-23 bearing WIV elicited the highest anti-viral IgA levels in serum and nasal washes. CONCLUSIONS: This study highlights for the first time the mucosal adjuvant potential of IL-12 and IL-23 CYT-IVAC formulations in eliciting mucosal immune responses and reducing viral lung burden. The co-presentation of immunomodulators in direct context with viral antigen in whole inactivated viral vaccines may provide a means to significantly lower the dose of vaccine required for protection.